دور رعاية البرامج التربوية الخاصة في تحقيق السلوك التكيفي - خنيش, ليلى (جامعة الوادي - University of Eloued, 2023)
هدف هذا البحث إلى إبراز الدور الذي تلعبه برامج الرعاية التربوية الخاصة في تحقيق السلوك التكيفي لدى الأطفال ذوي متلازمة داون، و توضيح كيف يمكن تنمية السلوك التكيفي داخل مراكز التربية الخاصة من خلال تلقي الأطفال التريزوميين لبرامج علاجية و تدريبية. وفي سياق الاجابة على إشكالية الدراسة تم إستخدام مقياس السلوك التكيفي ، وقد خضع المقياس إلى دراسة سيكومترية هدفت إلى تحقيق شرطي الصدق و الثبات. و طبق المنهج الوصفي على عينة الدراسة تضمنت عينة البحث 20طفلا من ذوي الاعاقة العقلية المتوسطة و المصابين بمتلازمة داون القابلون للتدريب(و تتراوح نسب ذكائهم ما بين (55-35درجة، و تم تحديد نسب ذكائهم بناء على (نتائج مصفوفات ريفن ). Abstract: The aim of this research is to highlight the role that special educational care programs play in achieving adaptive behavior in children with Down syndrome, and to clarify how adaptive behavior can be developed within special education centers through trisomic children receiving treatment and training programs. In the context of answering the problem of the study, the adaptive behavior scale was used, and the scale was subjected to a psychometric study aimed at achieving the conditions of honesty and stability. The descriptive approach was applied to the study sample. The research sample included 20 children with moderate mental disabilities and those with Down syndrome who are able to be trained (and their IQ ranges between (55-35 degrees), and their IQ ratios were determined based on (Results of Raven’s Matrices- (PMC). PM 47)
لدى الاطفال ذوي متلازمة داون
مقال
Keywords: التربية الخاصة ; البرامج التربوية ; السلوك التكيفي ; المتخلفين ذهنيا ; متلازمة داون; special education, educational programs, adaptive behavior, mentally retarded, Down syndrome